ANGI-01 ALTERATION IN IMMUNE REGULATORY CELLS BEFORE AND AFTER TREATMENT BY STUPP REGIMEN WITH OR WITHOUT BEVACIZUMAB FOR GLIOBLASTOMA. (16th December 2019) - Tanaka, Toshihide; Tamura, Ryota; Yamamoto, Yohei; Morimoto, Yukina; Teshigawara, Akihiko; Tochigi, Satoru; Hasegawa, Yuzuru; Takei, Jun; Akasaki, Yasuharu; Sasaki, Hikaru; Murayama, Yuichi
Abstract: BACKGROUND: In our previous study, bevacizumab (Bev), a humanized anti- vascular endothelial growth factor monoclonal antibody, downregulated the expression of programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) immune checkpoint molecules, suppressed the infiltration of immunosuppressing cells such as regulatory T cells (Tregs) and tumor-associated macrophages (TAMs), and induces cytotoxic T lymphocytes (CTL) infiltration. To explore the possibility that inhibition of immunosuppressive cell infiltration and induction of CTL were attributed to not only Bev alone but also radiation (RT) or temozolomide (TMZ), we re-evaluated those alterations in the tumor tissue obtained from patients before and after the treatment using Stupp regimen (RT concomitant with TMZ) without Bev therapy. MATERIALS & METHODS: We analyzed 10 tumor tissues from 5 patients with GBMs, which were paired samples of pre- and post- standard chemoradiotherapy (Stupp regimen: RT plus concomitant and adjuvant TMZ). Immunohistochemical analyses were performed on formalin-fixed, paraffin-embedded tissue of 10 tumors. The sections were stained with anti-Ki-67, anti-VEGF-A, anti-VEGFR1, anti-VEGFR2, anti-CD34, anti-HIF1 alpha, anti-CA9, anti-nestin, anti-PD-1, anti-PD-L1, anti-CD4, anti-CD8, anti-Foxp3, and anti-CD163 antibodies. All expressions were assessed by authors with blinded clinical information. RESULTS: Immunohistochemical analyses demonstrated that the expression levels of immune regulatory molecules such as Foxp3, CD163, PD-1, PD-L1, CD4, and CD8 were not significantly changed after the treatment using the Stupp regimen, compared with combinational usage of Bev. In addition, expressions of VEGF/VEGFR, hypoxic markers, and stem cell marker were not altered before and after Stupp regimen, either. Bev persistently inhibited immune suppressive cells and immune checkpoint molecules via down-regulation of VEGF pathway. In contrast, Stupp regimen did not affect immune regulations and tumor microenvironment. CONCLUSION: These results suggested that immunosupportive effect was caused by Bev administration, leading to the novel combinational treatment strategies, in addition to Stupp regimen.